Co-Pyrolysis of Jatropha Curcas Seeds and HDPE Plastic for Bio-Oil Production - Tiara, Tiara; Dzakwan, Akhmad; Mayasari, Rizka; Ulya, Muhamad Ridho; Haviz, Muhammad; Utari, Ririn (PUI BiGME Universitas Jambi, 2026)
The limited availability of fossil fuels and the growing volume of plastic waste underscore the need to develop environmentally friendly alternative energy sources. This study aims to produce high-energy-value bio-oil through a co-pyrolysis process involving Jatropha curcas seed biomass and high-density polyethylene (HDPE) plastic. The research involved the following stages: characterization of Jatrofa curcas seed, raw material preparation, pyrolysis, and analysis of bio-oil. The temperature variations used were 350°C, 450°C, and 550°C with raw material ratios of 75:25, 50:50, and 25:75. The results of the study indicate that increases in temperature and the proportion of HDPE significantly affect the increase in heat value and the decrease in moisture content of the bio-oil. The highest calorific value was obtained at a 25:75 ratio and a temperature of 450°C, amounting to 42.50 MJ/kg, while the lowest moisture content was 2.9% under the same conditions. This indicates a synergistic effect between the biomass and the plastic, in which HDPE acts as a hydrogen donor that reduces the oxygen content in the bio-oil, thereby improving the fuel quality. In conclusion, the co-pyrolysis method using Jatropha curcas seed and HDPE can produce bio-oil with better energy characteristics and low moisture content. This research not only contributes to the development of renewable energy but also offers innovative solutions for the sustainable management of plastic waste.